Synthesis and QSAR Studies of Novel Pyrazoline Derivatives as Antiproliferative Agent - Sable, Prafulla Madhukarrao; Sayyad, Nusrat Bhuru Ali (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Regardless of recent advances in the biological processes leading to the development of cancer, there is still a need for new and effective agents to help bring this disease under control. The revelation of the anticancer properties of pyrazoline makes this scaffold remarkable for research and development as an anticancer. Methods: A series of synthetic chalcones and pyrazoline derivatives were synthesized, characterized IR, 1H NMR and mass spectral analysis and evaluated for their Anticancer activity on MCF-7 cell line through SRB assay. A QSAR study was performed on thirtyfive compounds of known series having pyrazoline nucleus using Accelrys Discovery Studio Vs 2.1.0.8130. Results: We found that significant inhibitory activity among all the synthesized compound 1B showing better anticancer activity having IC50 value 0.010 μM as compared to standard drug letrozole. So predicted molecules from the QSAR study show significant activity. Conclusion: We would conclude that compound 1B might serve as a potential antiproliferative agent.
Keywords: Pyrazoline; QSAR; SRB assay; MCF-7; Antiproliferative activity